Spatial tactile localization depends on sensorimotor binding: preliminary evidence from virtual reality - Girondini, Matteo; Montanaro, Massimo; Gallace, Alberto (Frontiers in Human Neuroscience, 2024)
Introduction Our brain continuously maps our body in space. It has been suggested that at least two main frames of reference are used to process somatosensory stimuli presented on our own body: the anatomical frame of reference (based on the somatotopic representation of our body in the somatosensory cortex) and the spatial frame of reference (where body parts are mapped in external space). Interestingly, a mismatch between somatotopic and spatial information significantly affects the processing of bodily information, as demonstrated by the “crossing hand” effect. However, it is not clear if this impairment occurs not only when the conflict between these frames of reference is determined by a static change in the body position (e.g., by crossing the hands) but also when new associations between motor and sensory responses are artificially created (e.g., by presenting feedback stimuli on a side of the body that is not involved in the movement). Methods In the present study, 16 participants performed a temporal order judgment task before and after a congruent or incongruent visual-tactile-motor- task in virtual reality. During the VR task, participants had to move a cube using a virtual stick. In the congruent condition, the haptic feedback during the interaction with the cube was provided on the right hand (the one used to control the stick). In the incongruent condition, the haptic feedback was provided to the contralateral hand, simulating a sort of ‘active’ crossed feedback during the interaction. Using a psychophysical approach, the point of subjective equality (or PSE, i.e., the probability of responding left or right to the first stimulus in the sequence in 50% of the cases) and the JND (accuracy) were calculated for both conditions, before and after the VR-task. Results After the VR task, compared to the baseline condition, the PSE shifted toward the hand that received the haptic feedback during the interaction (toward the right hand for the congruent condition and toward the left hand for the incongruent condition). Dicussion This study demonstrated the possibility of inducing spatial biases in the processing of bodily information by modulating the sensory-motor interaction between stimuli in virtual environments (while keeping constant the actual position of the body in space).